Facile Gold-Nanoparticle Boosted Graphene Sensor Fabrication Enhanced Biochemical Signal Detection - Shuaishuai Meng; Li Wang; Xixi Ji; Jie Yu; Xing Ma; Jiaheng Zhang; Weiwei Zhao; Hongjun Ji; Mingyu Li; Huanhuan Feng (Nanomaterials, 2022)
Graphene has been considered as an excellent biochemical sensors’ substrate material because of its excellent physical and chemical properties. Most of these sensors have employed enzymes, antibodies, antigens, and other biomolecules with corresponding recognition ability as recognition elements, to convert chemical signals into electrical signals. However, oxidoreductase enzymes that grow on graphene surfaces are affected significantly by the environment and are easily inactivated, which hinders the further improvement of detection sensitivity and robusticity. A gold-boosted graphene sensor was fabricated by the in situ electrochemical deposition of inorganic gold nanoparticles on vertical graphene nanosheets. This approach solves the instability of biological enzymes and improves the detection performance of graphene-based sensors. The uric acid sensitivity of the gold-boosted electrode was 6230 µA mM−1 cm−2, which is 6 times higher than the original graphene electrode. A 7 h GNSs/CC electrode showed an impressive detection performance for ascorbic acid, dopamine, and uric acid, simultaneously. Moreover, it exhibited a reliable detection performance in human serum in terms of uric acid. The possible reason could be that the vertical aliened graphene nanosheet acts as a reaction active spot. This 3D graphene-nanosheet-based doping approach can be applied to a wide variety of inorganic catalytic materials to enhance their performance and improve their durability in aspects such as single-atom catalysis and integration of multiple catalytic properties.